HCV and HIV co-infection among people who inject drugs in Vietnam - Vu Toan THINH; Li LI; Dréan MATTHIEU; Van Dinh HOA; Nguyen Huu ANH; Le Minh GIANG (Journal of Health and Social Sciences)
Introduction: HIV/HCV co-infection in people who inject drugs (PWID) continues to be a major chal- lenge for health care systems and the PWID themselves. PWID have driven the HIV epidemic in Vietnam but information on HIV/HCV co-infection is limited. Methods: A cross-sectional study was conducted with 509 PWID recruited in Hanoi from February 2016 to April 2017. Four mutually exclusive groups were defined based on the presence of detectable HCV RNA and positive HIV confirmation. Multiple logistic regression analyses were performed to explore life-time risk behaviors of HCV mono-infection and HIV/HCV co-infection. Results: The overall prevalence of HIV and HCV infection was 51.08% and 61.69%, respectively. The prevalence of HCV mono-infection and HIV/HCV co-infection was 22.59% and 39.1%, respectively. We found that engaging in methadone maintenance treatment (MMT) was positively associated with HCV mono-infection (aOR = 2.38, 95% Confidential Interval [CI] 1.07 to 5.28) and with at least either HIV or HCV infection (aOR = 2.22, 95% CI 1.08 to 4.56). Ever being incarcerated was significantly associated with HCV mono-infection (aOR = 2.56, 95% CI 1.33 to 4.90) and HIV/HCV co-infection (aOR = 1.90, 95% CI 1.04 to 3.46). Those who had ever shared with and reused syringes/needles were more likely to have HIV/HCV co-infection (aORs = 5.17 and 2.86, P < 0001, respectively) and have either HIV or HCV infection (aORs = 3.42 and 2.37, P < 0001, respectively). Conclusion: Correlates for HCV mono-infection and HIV/HCV co-infection highlight the need to ad- dress risk behaviors, expand MMT programs, and establish HCV sentinel surveillance. The high prevalence of HCV and/or HIV co-infection shows a need for access to HCV treatment.